Prospects of charge signal analyses in liquid xenon TPCs with proportional scintillation in the liquid phase. (1st March 2022) - Kuger, F.; Dierle, J.; Fischer, H.; Schumann, M.; Toschi, F.
Abstract: As liquid xenon TPCs increase in target mass while pursuing the direct detection of WIMP dark matter, the technical challenges arising due to their size call for new solutions and open the discussion on alternative detector concepts. Proportional scintillation in liquid xenon allows for a single-phase design evading problems related to the liquid-gas interface and the precise gas gap required in a dual-phase TPC. Aside from a different scintillation mechanism, the successful detection- and analysis scheme of state-of-the-art experiments is maintained in this approach. We study the impact on charge signal analysis in a single-phase detector of DARWIN dimensions, where the fast timing of the proportional scintillation signal allows for the precise identification of the single electrons in the ionisation signal. Such a discrete electron-counting approach can lead to a better signal resolution for low energies when compared to the classical dual-phase continuous method. The absence of the liquid-gas interface can further benefit the S2-only energy resolution significantly. This can reduce the uncertainties from the scintillation and signal-detection process to a level significantly below the irreducible fluctuation in the primary ionisation. Exploiting the precise electron arrival time information can further allow for a powerful single vs. multiple site interaction discrimination with 93% rejection efficiency and 98% signal acceptance. This outperforms the design goal of the DARWIN observatory by a reduction factor of 4.2 in non-rejected multiple site neutron events.